Paleogene paleoclimate record in Artic high latitudes - Salpin, Marie (HAL CCSD, 2017)
The Palaeogene is a period of major climate system disturbances, especially marked by climatic optima recognized in both continental and marine environments. In the context of current global warming, the study and understanding of this period of strong climate fluctuations and transition between a greenhouse and an icehouse world is a major issue. Numerous studies have been conducted on low and mid latitudes, while only few studies focus on high latitudes. In this study, Paleocene-Eocene deltaic successions are used to study the response of the Arctic system to global events, the Paleogene climatic optima (PETM, ETM2, EECO and the Azolla event) and attempt to respond to these questions: did the basin have a specific response to global climate stimuli? Are there coupling / decoupling mechanisms between the dynamics of the Arctic basin and the global ocean? This study is based on multiproxies analysis: bulk and clay mineralogy, Rock Eval pyrolysis, palynology, palynofacies and stable isotopes of organic carbon. The results suggest warming episodes allowing the installation of mangroves in the Arctic Basin in an already warm climate. In the Northwestern Territories, mineralogical results suggest local fluctuations in detritic sources controlled by tectonics and / or eustatism and may overlap with the climate record. Le Paléogène est une période de perturbations importantes du système climatique terrestre, marquée notamment par des optima climatiques reconnus à la fois en environnement continental et marin. Dans le contexte de réchauffement climatique actuel, l’étude et la compréhension de cette période de fortes fluctuations climatiques et de transition entre un climat de type « greenhouse » et « icehouse » est un enjeu capital. Par ailleurs, de nombreuses études ont été menées sur les basses et moyennes latitudes, alors que peu de travaux se focalisent sur les hautes latitudes. Dans cette étude, des successions deltaïques d’âge Paléocène-Eocène sont utilisées pour étudier la réponse du système Arctique à des ...